Far Infrared near normal specular reflectivty of Nix(SiO2)1-x (x=1.0,0.84,0.75,0.61,0.54,0.28) granular films - Massa, Nestor Emilio (2010)
One of the current issues at the basis of the understanding of novel materials is the degree of the role played by spatial inhomogeneities due to subtle phase separations. To clarify this picture here we compare the plain glass network response of transition metal granular films with different metal fractions against what it is known for conducting oxides Films for Nix(SiO2)1-x ,x= 1.0, 0.84,0.75, 0.61,0.54, 0.28, were studied by temperature dependent far infrared measurements. While for pure Ni the spectrum shows a flat high reflectivity, those for x ~0.84 and ~0.75 have a Drude component, vibrational modes mostly carrier screened, and a long tail that extents toward near infrared. This is associated with hopping electron conductivity and strong electron-phonon interactions. The relative reduction of the number of carriers in Ni0.75(SiO2)0.25 allows less screened phonon bands on the top of a continuum and a wide and overdamped oscillator at mid-infrared frequencies. Ni0.54(SiO2)0.46 and Ni0.28(SiO2)0.72 have well defined vibrational bands and a sharp threshold at ~1450 cm-1. It is most remarkable a distinctive resonant peak at 1250 cm-1 found for p-polarized angle dependent specular reflectivity. It originates in an electron cloud traced to electrons that are not able to overcome the metal-dielectric interface that, beating against the positive background, generates the electric dipole. Overall, we conclude that the spectra are analogous to those regularly found in conducting oxides where with a suitable percolating network polarons are formed.